The royal assassin - Parker, Kate, 1949- (Parker, Kate, 1949- Victorian bookshop mystery., 2015)
"When the Duke of Blackford enter her bookstore, Georgia know the Archivist Society is in need of her services. The tsar of Russia and his family are visiting Queen Victoria on the auspices of the engagement of the Russian princess Kira to the son of the queen's cousin. When Kira's bodyguard is found dead on a train returning from Scotland, the queen calls on Blackford to discreetly protect the princess and prevent an international incident."